Impact of past steel-making activities on lanthanides and Y (REY) fractionation and potential mobility in riverbank sediments - Hissler, Christophe; Montarges-Pelletier, Emmanuelle; Kanbar, Hussein J.; Le Meur, Mathieu; Gauthier, Christophe (Frontiers in Earth Science, 2023)
New technologies significantly disturb the natural riverine cycle of some Rare Earth Elements and Yttrium (REY). Whereas large evidence exists on the anthropogenic impact on REY dissolved and colloidal loads in rivers, there is still a knowledge gap on how suspended load could be impacted. As the river suspended matter is a key driver for the quantity of trace metal transport and mobility toward the other river compartments, it is of importance to evaluate how anthropogenic activity could affect its REY composition. Here, we report how past steel-making processes impacted the REY composition and potential mobility in riverbank sediments collected from a French River basin heavily disturbed by this industrial activity. In comparison to sediment originated from the local soil erosion, the industrial waste released in the river presented very unusual REY patterns. We observed specific LaN/GdN, LaN/LuN and Y/Ho ratios that indicate a strong heritage in the industrial waste of the iron ore used to produce steel. REY enrichments were also highlighted and can be classified as follow: Eu>Yb>Sm>Ce>Tm. The different enrichments might illustrate various fractionation processes that occurred separately on the different lanthanides inside the blast furnace according to temperature, pressure and oxygen fugacity changes. Sequential extractions performed on natural and industrial waste samples showed that REY enrichments in the industrial waste are included in one main fraction, which is strongly labile, whereas REYs contained in the sediment originating from the soil erosion are related to different mineralogical fractions having lower and more specific lability. Finally, REY composition showed that the sediment deposited on the riverbank is composed of two types of materials, which progressively evolved, after the ending of the industrial activity in this region, from a pure industrial waste in depth to a pure natural suspended sediment originated from local soil erosion at the surface.